Obesity and Blood Pressure in 17-Year-Old Offspring of Mothers with Gestational Diabetes: Insights from the Jerusalem Perinatal Study. (24th July 2011) - Avgil Tsadok, Meytal; Friedlander, Yechiel; Paltiel, Ora; Manor, Orly; Meiner, Vardiella; Hochner, Hagit; Sagy, Yael; Sharon, Nir; Yazdgerdi, Shoshanah; Siscovick, David; Elchalal, Uriel
Abstract : Objective . Gestational diabetes mellitus (GDM) influences fetal development and offspring's metabolic risk. We evaluated this association in 17-year-old offspring adjusting for birth weight (BW) and prepregnancy maternal BMI (mBMI). Study Design . The JPS birth cohort contains extensive data on 92, 408 births from 1964 to 1976. Offspring's BMI and blood pressure (BP) were obtained from military records. For a subcohort born between 1974 and 1976, prepregnancy mBMI was available. Offspring were classified as born to mothers with GDM (n = 293 ) or born to mothers without recorded GDM (n = 59, 499 ). Results . GDM offspring had higher mean BMI and systolic and diastolic BP compared to no-recorded-GDM offspring. After adjusting for BW, GDM remained significantly associated with offspring BMI and diastolic BP (β = 1.169 and 1.520, resp.). In the subcohort, when prepregnancy mBMI was entered to the models, it markedly attenuated the associations with GDM. Conclusions . Maternal characteristics have long-term effects on cardiometabolic outcomes of their offspring aged 17 years.